2021
DOI: 10.3390/molecules26134085
|View full text |Cite
|
Sign up to set email alerts
|

Hypocholesterolemic Effect of Blackcurrant (Ribes nigrum) Extract in Healthy Female Subjects: A Pilot Study

Abstract: Blackcurrant extract (BCE) ameliorates dyslipidemia in menopausal model animals and in elderly women at a risk of dyslipidemia. However, it is unknown whether the daily intake of BCE can prevent lipid abnormalities in healthy individuals. Lipids are essential for the body, but they also cause arteriosclerosis. In this noncomparative pilot study, we examined the effects of BCE administered for 29 days on serum lipids in young healthy women. Blood samples were collected before and on days 4 and 29 after BCE inta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Moreover, we found that BCE effectively reduced lipid metabolism abnormalities, suggesting its use as an effective strategy in preventing atherosclerosis [29]. The daily intake of BCE exerts a hypocholesterolemic effect in healthy young women [30], and it can attenuate smoking-induced acute endothelial dysfunction and improve peripheral temperatures in young smokers [31]. These results suggest that the intake of BCE is effective in preventing atherosclerosis, not only in the context of menopause as observed in OVX rats, but also in men and women of all ages.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…Moreover, we found that BCE effectively reduced lipid metabolism abnormalities, suggesting its use as an effective strategy in preventing atherosclerosis [29]. The daily intake of BCE exerts a hypocholesterolemic effect in healthy young women [30], and it can attenuate smoking-induced acute endothelial dysfunction and improve peripheral temperatures in young smokers [31]. These results suggest that the intake of BCE is effective in preventing atherosclerosis, not only in the context of menopause as observed in OVX rats, but also in men and women of all ages.…”
Section: Introductionmentioning
confidence: 72%
“…Furthermore, we performed another study to verify the effects of BCE in humans, in which 12 young healthy women were administered BCE for approximately 1 month. The results showed that the levels of total cholesterol and very-low-density lipoprotein cholesterol decreased significantly, and the LDL cholesterol level showed a decreasing tendency [30]. Therefore, administration of BCE has the potential to reduce lipid metabolism abnormalities.…”
Section: Histological Analyses Of the Abdominal Aorta Of Bce-treated Kk-a Y Micementioning
confidence: 96%
“…Atherosclerosis is associated with dyslipidemia, including elevated TG, TC, LDL-C levels, and a low HDL-C level [ 29 ]. Dynamic lipid imbalance is closely associated with AS pathogenesis, which has become a critical determinant of the occurrence and development of AS.…”
Section: Discussionmentioning
confidence: 99%
“…Decrease the amount of hydroxymethylglutary-CoA reducates, limits the intake of cholesterol, and stimulates the absorption of lowdensity lipoprotein (Nanashima et al, 2021) Renal system Juice Higher citric acid and oxalic acid production and reduced neutrophils (PMN leukocytes)…”
Section: Extractmentioning
confidence: 99%
“…Blackcurrant has a long tradition of a secure application, as well as being thoroughly investigated for its significant health effects. Limited research has focused on the additional therapeutic properties of blackcurrant, like vasculoprotective properties (Horie et al, 2021 ), hypocholesterolemic impact (Nanashima et al, 2021 ), improvement in the oxidation of fat (Song et al, 2021 ), regulation in brain functioning (Gibson et al, 2020 ), gut microbiota regulation (Song et al, 2021 ), and decrease in postprandial blood sugar (Iizuka et al, 2018 ), in addition to these broadly researched therapeutic properties (e.g., anti‐inflammatory, neuroprotective activities, anti‐cancer impact, and antioxidant) (Figure 4 ). The results indicate that polyphenols exhibit antioxidant activity that reduces the probability of developing various non‐communicable chronic conditions (chronic inflammatory disorders, atherosclerosis, type 2 diabetes, neurodegenerative disorder, and certain type of cancer) (Serino & Salazar, 2018 ).…”
Section: Therapeutic Potentialmentioning
confidence: 99%